STRATEGY FOR DEVELOPING ISLAMIC RELIGIOUS EDUCATION IN IT VOCATIONAL SCHOOLS AL-IZHAR PEKANBARU: SOLUTIONS FOR OVERCOMING PROBLEMS AND FINDING DEVELOPMENT MODELS ISLAMIC EDUCATION - Syukri; Wedra Aprison (BiCED Proceeding, 2024)
This study examines the challenges and solutions in the development of Islamic Religious Education (PAI) at Al-Izhar IT Vocational School Pekanbaru, which is driven by the urgent need to improve the quality and relevance of Islamic education in the modern educational environment. Previous research has highlighted limitations in teaching methods and resources in Islamic Religious Education, which are often lacking in practical application and Character building aspects. However, this research has mostly focused on theoretical discussions, with little emphasis on practical and context-specific solutions. Therefore, this study aims to bridge this gap by presenting a practical model for PAI that answers cognitive and affective needs, which is in line with the contextual demands of Al-Izhar IT Vocational School Pekanbaru. This research uses a qualitative case study approach to gain an in-depth understanding of the unique challenges facing schools. Data was collected through in-depth interviews with teachers, students, and school administrators, supported by classroom observation and document analysis. These triangulation data sources are analyzed thematically to identify core issues in PAI delivery and to develop relevant solutions. The findings of the study revealed that the main challenges include limited classroom time allocation, traditional lecture-based teaching approaches, and inadequate educational resources. These factors collectively inhibit student engagement and limit the effectiveness of internalizing Islamic values. In response to these challenges, this study proposes the implementation of better project-based learning and teacher training programs. Project-based learning provides students with active learning opportunities that connect Islamic teachings with real-life applications, thus fostering a stronger understanding and practice of Islamic values. In addition, targeted professional development for teachers equips them with innovative pedagogical skills and technology integration strategies. The novelty of this research lies in its context-specific approach, which offers a practical model that can be a reference for other educational institutions that want to optimize Islamic Education.